The determinants of trade survival - Marco Fugazza; Ana Cristina Molina (Graduate Institute of International and Development Studies, 2009)
The aim of this paper is to explore the patterns of trade duration across regions and to identify its determinants. Using an extended Cox model, we evaluate the effects of country and product characteristics, as well as of trade cost variables on the duration of trade relationships from 96 countries from 1995 to 2004. Our results suggest first that the duration of trade relationships increases with the region level of development: trade relationships from richer economies face lower hazard rates i.e. longer duration. Second, the type of product matters for export survival, trade relationships involving differentiated products show a hazard rate that is 11% to 13% lower than trade relationships involving homogeneous goods. Third, high export costs increase the probability of export failure in all regions but the effect diminishes with time, thus suggesting that export experience matters. Finally, the size of exports also matters: the larger the transaction, the higher the probability of survival.
Keywords: F1; C41; 330; Duration; Trade; Fixed Costs; Internationale Wirtschaftsbeziehungen; Dauer; Produktdifferenzierung; Fixkosten; Schätzung; Welt